Makna Ceramah Ust Hanan Attaki: “Celah Syaitan Masuk Ke Dalam Hati Manusia” - Raden Fietra Universalia Adikusumah; Adela Futri Fiziani (Universitas Maritim AMNI Semarang, 2022)
This research reviews the meaning of Ust Hanan Attaki's lecture entitled